Clinical efficacy of benazepril and irbesartan for children with chronic glomerulonephritis - LIU Xiao-yan (Linchuang shenzangbing zazhi)
Objective To investigate the clinical effectiveness of the combined use of benazepril and irbesartan in children with chronic nephritis.Methods Sixty-eight cases of chronic glomerulonephritis were enrolled.All patients were randomly divided into experimental group and control group,34 cases in each group.The control group was treated with benazepril 10 mg/day,once every day.The experimental group was treated with benazepril(10 mg/day,once every day),and irbesartan(300 mg/day,once every day).Blood pressure,24-h urinary protein,urinary albumin excretion rate(UAER),serum creatinine(SCr),creatinine clearance rate(Ccr),urea nitrogen(BUN) and other related indicators were observed.Results In the experimental group,the marked effectiveness was obtained in 12 cases,and effectiveness in 18 cases with the total effective rate being 88.24%.In the control group,5 cases obtained marked effectiveness,and 17 cases obtained effectiveness with the total effective rate being 64.71%.The clinical efficacy of the experimental group was significantly better than that of the control group,and the differences were statistically significant(P<0.05).SCr levels were decreased more significantly in the experimental group than in the control group,and the difference was significant(P<0.05).In experimental group and control group,the mean UAER decreased to(312.7 ± 21.3) and(344.9 + 27.1) μg/min respectively(P<0.05).The urinary protein was decreased more significantly in the experimental group than in the control group,and the difference showed statistical significance(P<0.05).There was no significant difference in the changes of Ccr and BUN(P>0.05).There was no significant difference in the systolic and diastolic blood pressure between two groups(P>0.05).There was no significant difference in adverse reaction rate between two group(P>0.05).Conclusions Combination of benazepril and irbesartan in the treatment of children with chronic nephritis is better than the single use of benazepril.